2008
DOI: 10.1111/j.1574-6941.2008.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification in terrestrial hot springs of Iceland and Kamchatka

Abstract: Archaea have been detected recently as a major and often dominant component of the microbial communities performing ammonia oxidation in terrestrial and marine environments. In a molecular survey of archaeal ammonia monooxygenase (AMO) genes in terrestrial hot springs of Iceland and Kamchatka, the amoA gene encoding the alpha-subunit of AMO was detected in a total of 14 hot springs out of the 22 investigated. Most of these amoA-positive hot springs had temperatures between 82 and 97 degrees C and pH range betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(133 citation statements)
references
References 33 publications
12
120
1
Order By: Relevance
“…Our results signify that all cultivated representatives of Group I Crenarchaeota to date synthesize crenarchaeol, thus providing support for the suggested specificity of crenarchaeol to Archaea involved in ammonia oxidation (de la Torre et al, 2008). Crenarchaeol has also been detected at sites of archaeal ammonia oxidation in the marine water column of the coastal North Sea (Wuchter et al, 2006), the Black Sea , Icelandic hot springs (Reigstad et al, 2008), Nevada and California hot springs (Pearson et al, 2004;Zhang et al, 2006;Pitcher et al, 2009) and agricultural soils (Leininger et al, 2006). Although Wuchter et al (2006) and Leininger et al (2006) found a strong correlation between crenarchaeol abundance and amoA copy numbers, but because of a lack of cultured representatives from Group I Crenarchaeota falling outside the recognized AOA, it yet cannot be unambiguously concluded that crenarchaeol synthesis is actually restricted to AOA.…”
Section: Discussionmentioning
confidence: 61%
“…Our results signify that all cultivated representatives of Group I Crenarchaeota to date synthesize crenarchaeol, thus providing support for the suggested specificity of crenarchaeol to Archaea involved in ammonia oxidation (de la Torre et al, 2008). Crenarchaeol has also been detected at sites of archaeal ammonia oxidation in the marine water column of the coastal North Sea (Wuchter et al, 2006), the Black Sea , Icelandic hot springs (Reigstad et al, 2008), Nevada and California hot springs (Pearson et al, 2004;Zhang et al, 2006;Pitcher et al, 2009) and agricultural soils (Leininger et al, 2006). Although Wuchter et al (2006) and Leininger et al (2006) found a strong correlation between crenarchaeol abundance and amoA copy numbers, but because of a lack of cultured representatives from Group I Crenarchaeota falling outside the recognized AOA, it yet cannot be unambiguously concluded that crenarchaeol synthesis is actually restricted to AOA.…”
Section: Discussionmentioning
confidence: 61%
“…De Boer and Kowalchuk (2001) found that Nitrosospira species, which are the most common AOB in soil (Kowalchuk et al, 2000), were not able to oxidize ammonium at pH values below 5.5. In contrast, several studies indicate that AOA are able to oxidize ammonium in a broad pH range (Leininger et al, 2006;Nicol et al, 2008;Reigstad et al, 2008) and appear to be better adapted to ammonium-poor environments (Di et al, 2009(Di et al, , 2010 and soils with low pH (Nicol et al, 2008).…”
Section: Plants As Competitors For Nutrientsmentioning
confidence: 94%
“…Thermophilic ammonia oxidation is fueling hydrothermal and geothermal life. Many archaeal ammonia monooxygenase subunit A (amoA) genes have been detected in high-temperature habitats such as deep-sea hydrothermal vents (Wang et al, 2009;Baker et al, 2012), subsurface thermal springs (Spear et al, 2007;Weidler et al, 2008) and terrestrial hot springs (Reigstad et al, 2008;Dodsworth et al, 2011). In addition to these oligotrophic ecosystems, the amoA gene was also found in nutrient-rich high-temperature engineered environments such as petroleum reservoirs and composting facilities (Zeng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%